Rapid acanthocytic schistocytosis and fulminant microangiopathic hemolysis as a preterminal event. Issue 5 (17th May 2021) - Moshref Razavi, Habib; Yu, Richard
Abstract: Isolated schistocytosis is a hematological emergency. Clinically significant schistocytosis requires 1% red cell fragments in a high power field. These include triangular fragments, crescents, helmet cells, keratocytes, or microspherocytes.